Transformational leadership and organizational citizenship behavior: Modeling emotional intelligence as mediator - Majeed Nauman; Ramayah T.; Mustamil Norizah; Nazri Mohammad; Jamshed Samia (Management şi Marketing, 2017)
Leadership and organizational citizenship behavior (OCB) stayed at pinnacle in the arena of organizational behavior research since decades and has attained significant consideration of scholars pursuing to define multifaceted dynamics of leadership and their influence on follower’s behavior at work. The voluntary behavior of Organizational citizenship improves organizational effectiveness, and it goes beyond formal job duties. This study attempts to explore the association amongst transformational leadership and organizational citizenship behavior of teachers in public sector higher education institutions in Pakistan. Study of organizational citizenship behavior in educational organizations and academicians is of high value that definitely requires attention. This study examines the direct and indirect influence of transformational leadership through exploring the mediating role of emotional intelligence. The model was tested by employing structural equation modelling technique on survey responses collected from academicians. Results from 220 responses indicated that relationship between transformational leadership and Organizational Citizenship Behavior is statistically significant where Emotional Intelligence plays an important role as a mediator. The results support and add to the positive effects of transformational leadership style interconnected with extra role behavior at work making it more meaningful. The findings make a significant contribution to leadership and organizational behavior literature in higher education sector and propose that organizations should implement practices that help in enhancing the level of organizational citizenship behavior in organizations.